Aram Kalantaryan - Melkonyan, Husik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The notable archaeologist and historian, Aram Kalantaryan, was a scholar completely devoted to his field. He was born in 1937 and raised by the family that had fled from Akn (historical Armenia) to Abkhazia during the Armenian Genocide. In 1954 he had entered the Department of History of Yerevan State University from which he graduated with high honors in 1959. From 1961-1964 he was a PhD student of archaeology at the Institute of Archaeology and Ethnography, Armenian Academy of Sciences. His advisor was the outstanding Armenologist Karo Ghafadaryan. A. Kalantaryan focused his research on medieval Armenian archaeology, history, and epigraphy. At that time he began to actively participate in the excavations (led by his advisor) at the important medieval Armenian capital of Dvin, which predetermined the future focus of his studies. A. Kalantaryan, from his days as a PhD student, participated in several excavations at important archaeological sites like Garni, Armavir, and Artashat. He was in charge of expeditions to Oshakan, Spitak, Ptghni, and Gogaran. In 1964 Kalantaryan was appointed as a junior researcher at the Department of Ancient and Medieval Archaeology of the Institute of Archaeology and Ethnography, Armenian Academy of Sciences. In 1966 he successfully defended his doctoral thesis entitled as ‘The Material Culture of Dvin (5th-8th centuries)’.